RNA in axons, dendrites, synapses and beyond - Taylor, Richard; Nikolaou, Nikolas (Frontiers in Molecular Neuroscience, 2024)
In neurons, a diverse range of coding and non-coding RNAs localize to axons, dendrites, and synapses, where they facilitate rapid responses to local needs, such as axon and dendrite extension and branching, synapse formation, and synaptic plasticity. Here, we review the extent of our current understanding of RNA subclass diversity in these functionally demanding subcellular compartments. We discuss the similarities and differences identified between axonal, dendritic and synaptic local transcriptomes, and discuss the reported and hypothesized fates and functions of localized RNAs. Furthermore, we outline the RNA composition of exosomes that bud off from neurites, and their implications for the biology of neighboring cells. Finally, we highlight recent advances in third-generation sequencing technologies that will likely provide transformative insights into splice isoform and RNA modification diversity in local transcriptomes.